PENGARUH PESAN IKLAN LAYANAN MASYARAKAT E-FILLING PADA VIDEO YOUTUBE DITJEN PAJAK RITERHADAP PERILAKU PENGARSIPAN ELEKTRONIK (Survei Pada Generasi Millenial Kota JakartaSelatan) - Fadhillah Alfansa Achmad (2020)
A large number of internet users in Indonesia accessing social media YouTube makes advertising keep abreast of technological developments so that these messages reach the right audience. This study aims to determine the effect of the delivery of the contents of the message about the E-filling Public Service Advertisements on the YouTube video of the Directorate General of Taxation on electronic archiving awareness (Survey on Millennial Generation of South Jakarta City). The concept or theory used in this study is the hierarchical theory of effects. This research uses a quantitative research approach. The research method used was a survey. The population in this study is the citizens of south Jakarta Millenials aged 20-34 years with a total of 100 samples. The sampling technique uses non-probability sampling which uses purposive sampling. The analysis technique of the effect of variable X on variable Y uses the coefficient of determination test. Data testing techniques were processed using SPSS (Statistical Product and Service Solution) version 26. The results of this study indicate that there is a correlation between E-filling public service advertisement messages on YouTube's video of Ditjen Pajak RI on awareness of electronic archiving and there is a strong influence between the two variables. These results are supported by hypothesis testing. H0 is rejected and Ha is accepted, which means that the greater the influence of E-filling public service ad messages on YouTube's Ditjen Pajak RI video, the higher the awareness of electronic archiving.